2022
DOI: 10.3991/ijep.v12i3.29497
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a Model for the Development of University Teacher Training Through Virtual Courses

Abstract: In times of pandemic, the education sector, worldwide, was affected. To minimize the problem, they carried out strategies that allow the start of virtual classes optimally. Likewise, teachers had to be trained, to be at the forefront of the context. Training should be asynchronous. In this sense, the objective of the research was to implement a model of teacher training through virtual courses. These courses are made up of the teaching-learning strategy, pedagogical resources and materials, the learning evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…According to the results, it was found that the VLLE on metaverse can be applied through VRChat application as media for self-learning and for public interaction in a university because it enables the students to feel as if they were in the real university environments. This is consistent with the research of Laberiano et al [23], who researched the creation of virtual courses for training. This can help foster self-learning and develop a vision of self-improvement.…”
Section: Results After Using Vlle On Metaversesupporting
confidence: 92%
“…According to the results, it was found that the VLLE on metaverse can be applied through VRChat application as media for self-learning and for public interaction in a university because it enables the students to feel as if they were in the real university environments. This is consistent with the research of Laberiano et al [23], who researched the creation of virtual courses for training. This can help foster self-learning and develop a vision of self-improvement.…”
Section: Results After Using Vlle On Metaversesupporting
confidence: 92%
“…Individual tutoring is carried out by the tutoring area according to personal demand, and it is the teachers, in their role as tutors, who offer students elements to cover their academic orientation needs. As a result of the pandemic, appropriate strategies had to be applied [26]. After carrying out the hybrid learning in times of pandemic, tutoring will partially return to face-to-face.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the emphasis in the context was primarily on the university's licensing rather than the accreditation of the individual programs. In addition, there are areas to improvement concerning the research skills of engineering students, particularly in writing and the effective utilization of technological tools [5] [6]. As a result, there has been a low production of theses and a limited number of graduates in the engineering programs.…”
Section: Introductionmentioning
confidence: 99%